The Evolution of Vulnerabiity in Norwegian Refugee Debates: Semantic and Political Changes over Four Decades - Lillevik, Ragna (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
This study traces how vulnerability emerged as a key concept in Norwegian refugee policy from the 1980s to the 2020s. Using Koselleck’s conceptual history framework, it analyzes seven major legislative and policy debates. The findings show a shift from systemic understandings of displacement to individualized assessments of risk, reinforcing hierarchies of deservingness. Vulnerability liberalized asylum procedures but also legitimized restrictive policies, favouring resettled refugees over asylum seekers. The study highlights how this concept operates as both a moral and a political tool, shaping refugee priorities while narrowing political responsibility for global displacement.